Kinerja Merger dan Akuisisi pada Perusahaan Go Public - Retno Ika Sundari (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2017)
This research aims to examine the effect of merger and acquisition firm performance at Indonesia Stock Exchange. Firm performance is measured by financial ratios: current ratio, quick ratio, return on investment, return on equity, debt to equity ratios, fixed assets turnover, operating profit margin, price book value, price earning ratio, and abnormal return around announcement date of merger and acquisition. Sample of this research is determined by purposive sampling method, consist of 27 Indonesia Stock Exchange excluded banking that did merger and acquisition from period of 2006-2011. This research analysis used Wilcoxon Signed Ranked Test for abnormal distribution data. The result of this research showed that financial ratios at 1 year before and 1 year after merger and acquisition are not all significant, except abnormal return variable, price book value and price earnings ratio indicated different significantly. This result indicated that merger and acquisition did not provide synergy for firms. Market reaction indicated that investor influenced by merger and acquisition of the firms and they believed that the announcement will give them hope about better future performance.